Frequency domain fluorescence microspectrometry: Application to cellular uptake and drug distribution. Issue 3 (2010) - Praus, Petr; Kocišová, Eva; Mojzeš, Peter; Štepánek, Josef; Sureau, Franck; Turpin, Pierre-Yves
Abstract : Time-resolved confocal microspectrofluorometry and fluorescence microimaging were used to monitor how the model antisense oligonucleotide is transported into 3T3 living cells and distributed inside them. Phosphorothioate analog of 15-mer oligothymidylate labeled by ATTO 425 was complexed with Zn(II) 5, 10, 15, 20-tetrakis(4-N-methylpyridyl) porphyrin as an uptake-mediating agent. Homodyne phase-resolved technique based on a high frequency analog modulation of both exciting diode laser and detector image intensifier was used for time-resolved measurements. Decay-time data obtained within a broad range spectral region have provided unique information about the fate of both fluorophores inside the cell.